Coaches' provision of structure for players' competence development: perspectives of professional soccer coaches and players in Norway - Nicol, K.; Allen, J. B. (International Sport Coaching Journal, 2025)
Developing athletes` actual and perceived competence is critical to enhancing performance and considered central to coaching. According to self-determination theory, the provision of competence-supportive structure is critical for psychological need satisfaction, optimal motivation, and well-being. Coaches use of structure such as providing clear expectations, instructional guidance, and feedback are well-established coaching practices; however, little is known about how, and to what extent, these types of structure support or thwart players` perceptions of competence, particularly in high-performance contexts. Five head coaches working in the highest soccer league in Norway, and three players from each of the participating head coach`s squads (N = 15) participated in semistructured interviews. Through abductive analysis, we generated five themes: structure to promote competence; coaching for competence development; relatedness support as a foundation for effective structure; freedom within structure is useful; and shared ownership of, and with, structure. The findings provide evidence that professional soccer coaches and players in this study desire and deliver structure. It is provided in an autonomy-supportive way and built on a relatedness supportive foundation. This study contributes new insight into the importance of competence-supportive structure in coaching, which coaches and those supporting the development of coaches may find useful.